2018
DOI: 10.1002/mus.26056
|View full text |Cite
|
Sign up to set email alerts
|

Guillain‐BarrÉ syndrome subtype diagnosis: A prospective multicentric European study

Abstract: Serial EDX has no effect on GBS subtype proportions. The absence of exclusive correlation with RCF and anti-ganglioside antibodies may challenge the concept of demyelinating and axonal GBS subtypes based upon electrophysiological criteria. Frequent RCF indicates that nodal/paranodal alterations may represent the main pathophysiology. Muscle Nerve, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 33 publications
0
27
1
Order By: Relevance
“…To situate our study, we reviewed the existing literature from 2000 to present, with regards to neurophysiological studies in GBS. Most studies have investigated neurophysiological findings that were conducted more than 5 days after disease onset [4][5][6]. Early diagnosis and proper treatment administered could obtain satisfactory prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…To situate our study, we reviewed the existing literature from 2000 to present, with regards to neurophysiological studies in GBS. Most studies have investigated neurophysiological findings that were conducted more than 5 days after disease onset [4][5][6]. Early diagnosis and proper treatment administered could obtain satisfactory prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, male sex was more prominent in terms of sex distribution in patients with GBS (6,12,13,14). In the studies reported from our country, it is observed that male patients are in the majority (11,15,16).…”
Section: Discussionmentioning
confidence: 49%
“…Of these, approximately 50% were associated with respiratory and gastrointestinal tract infections, and this was consistent with the literature. In large-scale studies, respiratory infections and gastrointestinal tract infections have been reported as the most common preceding infections with a rate of 37.8-80% (6,12,14,15,17). In accordance with the literature, the presence of gastroenteritis as a preceding infection was considered as a poor prognostic factor (7,18).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite several attempts to differentiate axonal GBS from AIDP using electrodiagnosis, no consensus has been achieved. The article in this issue of Muscle & Nerve by Van den Bergh et al 4 greatly helps in this debate.…”
mentioning
confidence: 99%
“…These was then modified to include temporal dispersion as a sign of segmental demyelination. The results of the study by Van den Bergh et al 4 were the following: (i) Comparing the initial EDX study to the second study did not change classification no matter what criteria was used. (ii) When comparing the different criteria, the Rajabally criteria had a lower percentage of demyelinating cases than the Ho or Hadden criteria which were similar (50% vs. 72.4% ).…”
mentioning
confidence: 99%